Clinico-pathological study of skin appendageal tumours from northern India - Jain, Preeti; Jain, Shailendra Kumar; Singh, Abhishek; Goel, Shewtank; Khichi, Sanjeev Kumar; Goyal, Pooja (International Journal of Research in Medical Sciences, 2016)
Background: The skin appendageal tumours (ATs) encompass a wide variety of tumours clinically presenting as papules and nodules and with histologically distinct features. Early recognition of skin adnexal tumours is very important aspect as far as patient management and prognosis is concerned. The main of the study was to analyse and ascertain clinico-pathological study of skin appendageal tumours in a tertiary care centre. Methods: Retrospective cohort of patients with confirmed diagnosis of AT during 1st January 2013 to 31st December 2015 formed the study population. Study tools were records of the patients such as information from MRD (Medical Record Department) and records from histopathological section i.e. histopathological requisition forms and clinical case sheets. Cases clinically diagnosed as appendageal tumours, but not histologically, were excluded from the study. Results: Finally a total of 48 cases were included in this study. Mean age of onset was 22.7±6.4 years and the duration of complaints 5.34 ± 4.5 years. Benign follicular, benign eccrine, benign sebaceous and benign apocrine tumours were observed to be 48.89%, 42.22%, 2.22% and 6.67% respectively. Regarding distribution of benign and malignant tumours, among the all types of skin appendageal tumours diagnosed, 93.75% (N=45) were benign and 6.25% (N=3) were malignant. Pilomatricoma (54.54%), eccrine acrospiroma (26.31%) and syringocystadenoma papilliferum (67%) were observed as most commonly distributed histopathological types of diagnosed benign follicular, benign eccrine and benign apocrine tumours. Number of benign skin appendageal tumours was found maximum (n=25) in the age group of 26-50 years in both the sexes whereas malignant skin appendageal tumours were observed only (n=3) in the age group of 51-75 years in both the sexes. Conclusions: Findings of this study can be utilized to suspect type of AT thus helping in diagnosis. Profile, pattern and clinical appearance can serve as vital clue though histological confirmation is mandatory to confirm.